INNOVATIVE METHODS - A NEW STYLE OF ORGANIZATION OF EDUCATIONAL AND COGNITIVE ACTIVITY OF STUDENTS - Eliseev Nikolai Alekseevich (Journals Park Publishing, 2023)
The traditional education system is somewhat behind the needs of society. The concept of modern education has determined the goal of a teacher's professional activity - to form students' ability for successful socialization in society, active adaptation in the labor market. The consequence of this is the development of innovative technologies in education. Innovative methods are characterized by a new style of organization of educational and cognitive activity of students. Innovations in education are innovations, innovations in the content of education, in the forms and methods of teaching, in the relationship "teacher - student", the use of information technology in education, the introduction of new equipment, in the organization of the educational process, its management, etc.
Keywords: strength, depth, efficiency, flexibility, efficiency, assessment, volume, level, quality, knowledge assimilation.